Attenuation of Extubation Reflexes with Lignocaine andPropofol following Laparoscopic Cholecystectomy – AQuasi-experimental Study (Journal of the Bangladesh Society of Anaesthesiologists, 2026)
Background: The purposeful removal of the endotracheal tube (Tracheal extubation) from the trachea, can be associated with detrimental airway and haemodynamic responses like an increase in coughing, bronchospasm, laryngospasm, heart rate, blood pressure, intracranial pressure, intraocular pressure and so on. Different extubation techniques and medications have been attempted for attenuation of the airway and cardiovascular responses. Propofol and Lignocaine are widely available drugs in resourcelimited settings and can be used to attenuate these responses and its complications. The objective of this study was to evaluate the effects of propofol and lignocaine in attenuating the extubation reflexes in patients undergoing laparoscopic cholecystectomy. Methods: This quasi-experimental study was carried out between March 2021 and April 2022 at Dhaka Medical College and Hospital. All enrolled participants were randomly allocated into three groups: Normal saline (Group A), Lignocaine 1mg/kg (Group B) and Propofol 0.5mg/kg (Group C). These medications were administered 2 min before extubation. Airway responses like (coughing, bucking, and laryngospasm), respiratory rate, oxygen saturation, and haemodynamic parameters (HR, SBP, DBP, and MAP) were recorded at different time intervals. Results: A total of 90 patients belonging to ASA I and II of either sexes (30 patients in each group) were included in this study. Demographic status and clinical characteristics of the patient were comparable among groups, with p-values > 0.05. After extubation, heart rate, systolic, diastolic, and mean arterial blood pressure were decreased significantly in propofol (Group C) and lignocaine (Group B) up to 15 min. A significant statistical difference was observed among the three groups in case of developing cough (pvalues = 0.002). Group C (propofol) showed a significant result in comparison with group B (lignocaine) (p-value = 0.001). There was no statistically significant difference found in case of SpO2 and respiratory rate among the groups and between the groups. (p-value > 0.05) Conclusions: Propofol is more effective than lignocaine in attenuating extubation reflexes. Propofol also reduces the incidence of post extubation airway complications.Bangladesh Society of Anaesthesiologists. 2023;36(2): 21-30